Reformasi dan Perlindungan Hak-hak Tahanan dan Narapidana di Lembaga Pemasyarakatan - Ach. Tahir (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
Prisoners under the law that undergoing criminal is the prisoners with noindependence in Prisons. The state's role in protecting the rights of detainees andcorrectional Prisoners as follows: performing worship according to religion or belief,getting treatment, both physical as well as spiritual care, education and teaching, gettinghealth care and decent food, making a complaint, obtaining materials reading andfollowing other mass media broadcasts which are not prohibited, receiving family visits,legal counsel, or other specified person, a reduction of the criminal (remission), getting achance to assimilate including holidays to visit family, getting parole and getting aheadof the holiday freely. Such rights must be given to the detainees and the Prisoners asnational efforts in rolling out protection for the rights of detainees and Prisoners. But theimplementation of such rights have not been exercised since the birth of the IndonesianGovernment Regulation No. 99 Year 2012 About Conditions and Procedures ofImplementation Team Building Correctional Rights. See the reality of the need toreform the bureaucracy in the Correction Board considering the habit of prolonging theprisoners in prison to prevent the granting of a Conditional Discharge (PB),assimilation, Holidays By Independent (CMB) and Visiting Family Leave (CMK)and lack of budget